Intermediate Accounting (Volume II) : Chapters 13-22 - Spiceland, J. David; Sepe, James F. and Tomassini, Lawrence A. (Boston, New York McGraw-Hill/Irwin, 2004)
Nettutor allows you to receive live,personalized tutoring via the internet.using nettutor 's powerful wwwwhiteboard software ,you can post a question and receive prompt feedback from an expoert in acccounting.
Include Index
Keywords: Accounting